The Reliability of Facial Recognition of Deceased Persons on Photographs. Issue 5 (15th February 2017) - Caplova, Zuzana; Obertova, Zuzana; Gibelli, Daniele M.; Mazzarelli, Debora; Fracasso, Tony; Vanezis, Peter; Sforza, Chiarella; Cattaneo, Cristina
Abstract: In humanitarian emergencies, such as the current deceased migrants in the Mediterranean, antemortem documentation needed for identification may be limited. The use of visual identification has been previously reported in cases of mass disasters such as Thai tsunami. This pilot study explores the ability of observers to match unfamiliar faces of living and dead persons and whether facial morphology can be used for identification. A questionnaire was given to 41 students and five professionals in the field of forensic identification with the task to choose whether a facial photograph corresponds to one of the five photographs in a lineup and to identify the most useful features used for recognition. Although the overall recognition score did not significantly differ between professionals and students, the median scores of 78.1% and 80.0%, respectively, were too low to consider this method as a reliable identification method and thus needs to be supported by other means.